FAKTOR FAKTOR YANG MEMPENGARUHI BELANJA MODAL DI PEMERINTAH KABUPATEN TABANAN - I MADE HARY KUSMAWAN; SUHARWAN HAMZAH; I GEDE ANGGA PERMANA (GANEC SWARA, 2023)
Since the reform in 1998, many new breakthroughs have emerged in advancing governance in Indonesia. The decentralization policy, which is hereinafter better known as the regional autonomy policy. With the enactment of this regional autonomy policy, it is hoped that regional financial independence can be realized. In this study the data analysis technique used was the classical assumption test, multiple linear regression, t test, F test. The results obtained were tcount (2.209) > ttable (1.782) and a significant level of 0.047 was greater than 0.05. Then Hi is accepted and H0 is rejected. This means that Regional Original Income partially has a positive and significant effect on Capital Expenditures. Because tcount (4.814) > ttable (1.782), then Hi is accepted and H0 is rejected with a significance level of 0.000. This means that the General Allocation Fund partially has a positive and significant effect on Capital Expenditures and tcount (5.380) > ttable (1.782), then Hi is accepted and H0 is rejected with a significance level of 0.000. This means that the Special Allocation Fund partially has a positive and significant effect on Capital Expenditure that Local Own Revenue, General Allocation Funds and Special Allocation Funds have an influence on capital expenditure. Because Fcount (47.051) > Ftable (3.49), then Ho is rejected and H1 is accepted with a significance level of 0.000. This means that regional original income, general allocation funds and special allocation funds have a significant effect simultaneously on capital expenditure.